SAKECO AGAINST SILENCE: PUBLIC FUNCTION ORAL TRADITION AS A SPACE FOR FREE EXPRESSION IN SUMBAWA SOCIETY - Suyasa, I Made (Prosiding Konferensi Internasional Kesusasteraan, 2025)
Sakeco, lawas oral tradition typical of the Sumbawa people, serves not only as entertainment but also as a medium of expression capable of raising marginalized voices amidst silenced social conditions. This paper aims to analyze Sakeco’s public function as a free space for expression in a society experiencing social repression, as well as its role as a tool to combat silence within the framework of marginal literature. Sakeco was chosen as a subject because of its ability to voice social and political criticism, especially in areas with power structures that suppress freedom of expression. Using Stuart’s theory of representation Hall, who emphasized the importance of popular culture as a space for the production of meaning, as well as Jürgen’s theory of the public sphere. Habermas stated that public space is a place where individuals can communicate freely and without pressure. This study explores how Sakeco functions as an alternative democratic space for marginalized communities to express themselves. This paper is based on literature studies and document analysis, which shows that Sakeco is able to affirm identity, strengthen social solidarity, and at the same time become a cultural strategy in fighting for freedom of expression. This paper provides new insights into the importance of oral traditions in maintaining freedom of expression and strengthening the position of marginal literature in the socio-political dynamics of society.